Design and Implementation of Dual Active Bridge Converter with Single Phase Shift Modulation for Electric Vehicle Charging System - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2021)
This article presents the implementation of a Dual Active Bridge converter with Single Phase Shift modulation, capable of controlling current and voltage at the converter output independently, through the design of simple PI controllers based on the model s transfer functions small phasor signal. It is validated in a 1 kW converter prototype, whose main passive components are designed and the graphs of the current and voltage controls at the output of the converter are obtained as an experimental result. © 2021 IEEE.